Optimizing calcium levels for oil palm seedlings in solution culture - Mayzaitul-Azwa, N. J.; Shuhada, N. M. T.; Hanafi, M. M.; Shittu, E. A. (International Journal of Agricultural Technology, 2025)
Oil palm seedlings grown in solution culture exhibited the best growth and physiological responses when treated with 1000 ppm calcium (Ca) from calcium chloride (CaCl₂). This concentration is significantly enhanced total biomass accumulation and improved vegetative parameters including seedling height, girth, root length, and number of leaves, compared to lower and higher Ca treatments. At 12 weeks, seedlings at 1000 ppm Ca showed significantly greater root length (27.08 cm), seedling height (41.85 cm), and girth (15.89 mm), alongside increased chlorophyll content (SPAD value of 55.48), indicating improved photosynthetic efficiency. Excess Ca (more than ≥ 2500 ppm) inhibited nutrient uptake, particularly nitrogen (N), phosphorus (P), and magnesium (Mg), due to antagonistic interactions, whereas 1000 ppm Ca maintained optimal macro-nutrient balance in both shoot and root sections. Ca concentration beyond this level led to reduced nutrient availability and poor growth performance, with 7000 ppm Ca showing the least favorable outcomes. The uptake of Ca was positively correlated with increased Mg concentration at optimal levels but decreased under excessive Ca conditions. The study demonstrated that 1000 ppm Ca not only optimizes growth parameters and biomass accumulation but also supports effective nutrient partitioning, making it the ideal concentration for oil palm seedling cultivation in hydroponic systems. These results provide critical insight for improving nutrient management strategies in oil palm nurseries to enhance early growth performance.